Evaluasi Pengelolaan Limbah B3 untuk Menunjang Penerapan Standar Keselamatan Kerja pada Perkantoran PT Ketenagalistrikan Kota Surabaya - Indah Sholihah Wulandari; Rizka Novembrianto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Management and characteristics of B3 waste at PT Ketenagalistrikan based on the potential hazards produced have been carried out by grouping and storing B3 waste based on physical, chemical and based on potential hazards with the aim of security and safety in the Temporary Storage Warehouse for B3 Waste. PT. Ketenagalistrikan has implemented a comprehensive Hazardous and Toxic Materials (B3) waste management system based on Government Regulation No. 22 of 2021 and Regulation of the Minister of Environment and Forestry No. 6 of 2021. Power plant operational activities produce various types of B3 waste such as used oil, used batteries, and other contaminated materials. B3 waste management is carried out through the stages of identification, sorting, containerization, labeling, temporary storage at licensed B3 TPS, as well as transportation and processing by licensed third parties. A quarterly recording and reporting system to environmental agencies is also carried out routinely. This program has succeeded in reducing the risk of environmental pollution and increasing the company's compliance with applicable B3 waste management regulations. Occupational Safety and Health (K3) at PT. Electricity, especially in the handling and storage of Hazardous and Toxic Materials (B3) waste, also plays an important role in avoiding unwanted things. B3 waste generated from PT. Ketenagalistrikan office operations such as used lubricants, batteries, used TL lamps, printer cartridges, and other electronic equipment require special handling in accordance with Government Regulation No. 22 of 2021. Compliance with K3 standards in the storage of B3 waste is an effort to minimize the risk of environmental pollution and potential health problems for workers. The implementation of K3 in the storage of B3 waste in PT. Ketenagalistrikan offices not only fulfills regulatory obligations but also supports the company's commitment to environmental sustainability in accordance with ISO 14001:2015, as well as ensuring the safety and health of its workers.